(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
The mother tongue education standard determines the mandatory volume of educational content determined by social demand in the mother tongue, as well as the volume of the educational load selected taking into account the age and level of development, needs and capabilities of students, and the requirements for the knowledge, skills, and qualifications of graduates of general secondary schools.